DINAMIKA HUBUNGAN INDONESIA DAN JEPANG DALAM INDONESIA JAPAN ECONOMIC PARTNERSHIP AGREEMENT STUDI KASUS: EVALUASI KEBIJAKAN TERHADAP EKSPLOITASI IKAN TUNA DI WILAYAH PERAIRAN INDONESIA - Larasati, Syntia Devi; Susetianingsih, Hermini; Paramasatya, Satwika (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2015)
Indonesia Japan Economic Partnership Agreement (IJEPA) is one ofthe economic cooperation agreed by Indonesia and Japan, regulatingabout tariff reduction. The study reveals that the economiccooperation conducted by both countries has certain implications forefforts in doing environmental reforms in Indonesia especially in thecase of tuna exploitation where these implications are believed to beable impact the relationship between Indonesia and Japan. Thisresearch is aimed to evaluate said impact on the environment as wellto take a closer look at the IJEPA bilateral relations of both countries.The results of this research indicate that the strategy of Indonesia’sperformance in such cooperation is moderately weak.